Взаимосвязь нейровегетативных расстройств с компонентами метаболического синдрома у пациентов с ишемической болезнью сердца - Михайловская, Н. С.; Кулинич, Т. О.; Шершнева, О. В.; Лисовая, О. А.; Грицай, А. В.; Михайловська, Наталія Сергіївна; Кулинич, Таміла Олегівна; Шершньова, Оксана Володимирівна; Лісова, Оксана Олександрівна; Грицай, Ганна Володимирівна; Mykhailovska, N.; Kulynych, T.; et al. (My University, 2021)
С целью установить взаимосвязь тревожно-депрессивных расстройств с компонентами метаболического синдрома у пациентов с ишемической болезнью сердца обследован 81 пациент с диагнозом ИБС – стабильная стенокардия напряжения I–III функционального класса: 1-я группа – 35 пациентов с ИБС, 2-я группа – 46 пациентов с ИБС в сочетании с метаболическим синдромом. С помощью суточного мониторирования ЭКГ, Сиэтловского опросника качества жизни, опросника SF-36, шкалы HADS исследованы клинические особенности пациентов с ишемической болезнью сердца во взаимосвязи с выраженностью тревожно-депрессивных расстройств. Установлено, что течение ИБС, коморбидной с метаболическим синдромом, ассоциировано с симпато-парасимпатическим дисбалансом, снижением качества жизни, более высокими суммарными уровнями тревоги и депрессии по шкале HADS, коррелирующими с такими компонентами метаболического синдрома, как абдоминальное ожирение, дислипидемия и гипергликемия. In order to reveal the relationship of anxiety-depressive disorders with the components of metabolic syndrome in patients with ischemic heart disease, 81 patients with the diagnosis of ischemic heart disease were examined – stable exertional angina of the II-III functional class: group 1 – 35 patients with ischemic heart disease, group 2 – 46 patients with ischemic heart disease in combination with metabolic syndrome. Using daily ECG monitoring, the Seattle quality of life questionnaire, the SF-36 questionnaire, the HADS scale, the clinical features of patients with coronary heart disease in relation to the severity of anxiety-depressive disorders were investigated. It was found that the course of coronary artery disease, comorbid with metabolic syndrome, is associated with sympatheticparasympathetic imbalance, decreased quality of life, higher total levels of anxiety and depression on the HADS scale, correlating with such components of metabolic syndrome as abdominal obesity, dyslipidemia and hyperglycemia.
Relationship between neurovegetative disorders and metabolic syndrome components in patients with coronary heart disease
Keywords: нейровегетативные расстройства; ишемическая болезнь сердца; метаболический синдром; neurovegetative disorders; coronary heart disease; metabolic syndrome